Promoting children’s achievement in mathematics using literacy strategies: A school-based intervention to increase parental involvement in children’s mathematical learning - Steiner, Lilly; Rizzuto, Kerry; Zambak, Vecihi (Journal of Interdisciplinary Studies in Education, 2024)
This study provides a model of a school-based, parent intervention to support parents in building children’s mathematics understanding at home. Participating parents received instruction in how to support elementary children’s mathematical homework, using literacy strategies. The researchers designed and implemented a five-week model with the goal to improve students’ mathematics performance through support that parents provided at home. The goal of the study was to investigate the effects of a literacy-focused, parent intervention on participating families’ ability to support their children’s school-based mathematical needs. Data collection included parent interviews, pre- and post-intervention, and audio recordings of parent-child work sessions in the home. This study contributes to the literature by providing a model for parents to utilize literacy skills to facilitate students’ mathematical understanding.